Paul de Man in etična literarna veda - Virk, Tomo (Primerjalna književnost, 2017)
The article discusses Paul de Man's contribution to the ethical literary criticism. It briefly presents his discussion of literature and ethics on various occasions and focuses on the notorious passage from the Allegories of Reading, famous for its opacity. It examines a series of its interpretations and finally scrutinizes the most influential among them, proposed by Hillis Miller in The Ethics of Reading. It is demonstrated that all these interpretations miss the point of the passage in question, the main reason for this being non distinguishing between the two levels of ethics in de Man's treatise and consequently mistakenly merging them together. The article proposes a close reading of the passage. It also pays attention to lacunas in de Man's argumentation that additionally complicate the comprehension of the passage. In conclusion, the article states that due to its opacity and idiosyncrasy, de Man's conception of the ethics of tropes remains basically unapplied in the ethical literary criticism.
Keywords: alegorija; allegory; De Man, Paul, 1919-1983; ethical literary criticism; etična literarna veda; Hillis Miller, Joseph; literatura in etika; literature and ethics